Kebutuhan dan Ketersediaan Aplikasi Mobile-Learning Video Pembelajaran Berbasis ESD Untuk Guru Sekolah Dasar - Lastri Lestari; Ghullam Hamdu (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Abstract: The purpose of this study was to find information about the needs of elementary school teachers in ESD-based learning and the availability of mobile learning applications for ESD-based learning videos as learning references. The descriptive method used is interviews with elementary school teachers, and literature study. The results show that teachers still have difficulty in obtaining ESD-based learning reference sources, both through mobile learning applications and learning implementation videos accompanied by complete learning tools. The availability of mobile learning applications for ESD-based learning videos in particular is not yet available either in schools or other sources commonly used by elementary school teachers to find reference sources for learning implementation. However, there has been the development of similar mobile learning applications but in different discussion and learning materials.